An ideographic study of bisexuality - Parker, Peter Burns (Rhodes University, Faculty of Humanities, Department of Psychology, 1977)
This research can be seen as being a step towards an answer to the question "what is bisexuality?". Such an aim, however, appears to be a contradiction in terms. Surely we must be assuming an answer by asking the question. How can one ask a question such as "what is bisexuality?", if we have no conception of what the word bisexuality means? Owing to the lack of information in the literature with which to answer the question of this study, it was decided that an in-depth study of one individual would be a most suitable starting point to begin an illumination of the themes which lie in the depths of this complex phenomenon . An in-depth study would hopefully do this without lapsing into the stereo - typed ways of thinking and terminology that could eventuate from a more populous and necessarily more superficial approach (Kotze 1974). Arising out of the prevailing conception of human sexuality as comprising two modes of sexual existence - heterosexuality and homosexuality only, the idea of bisexuality is hardly to be found in the ordinary man's or, for that matter, the psychologist 's, conceptual frameworks. The only extensive work that has been undertaken to date which uncovers, to a certain extent, the nature of human sexuality, is that of Kingsley (1948 and 1953). Although it must be kept in mind that this research is dated, it certainly does indicate that perhaps it would not be unrealistic to begin to reconceptualise our views on man's sexual mode of existence . This thesis presents the case of a man, who, according to our present view, does not exist.
Keywords: Bisexuality -- Psychological aspects